Retrieving high‐resolution tropospheric gradients from multiconstellation GNSS observations. Issue 10 (20th May 2015) - Li, Xingxing; Zus, Florian; Lu, Cuixian; Ning, Tong; Dick, Galina; Ge, Maorong; Wickert, Jens; Schuh, Harald
Abstract The developing multi‐Global Navigation Satellite Systems (GNSS) constellations have the potential to provide accurate high‐resolution tropospheric gradients. Such data, closely linked to strong humidity gradients accompanying severe weather phenomena, are considered a new important data source for meteorological studies, e.g., nowcasting of severe rainfall events. Here we describe the development of a multi‐GNSS processing system for the precise retrieval of high‐resolution tropospheric gradients. The retrieved products were validated by using independent water vapor radiometer (WVR) observations and numerical weather model (NWM) data. The multi‐GNSS high‐resolution gradients agree well with those, derived from NWM and WVR, especially for the fast‐changing peaks which were mostly associated with synoptic fronts. Compared to GPS‐only gradients, the correlations with the validation data are significantly improved up to 20–35%. The new data product has significant potential to improve numerical weather prediction and to advance meteorological studies.